Alkalinity–silicon ratio as an assessment factor for the efficiency of silicate slags in wetland rice - Thoppil Sreenivasan Sandhya (Nature Portfolio, 2021)
Abstract Silicate slags are one of the most widely used silicon (Si) source in agriculture. Even though the agronomic significance of slags has been demonstrated in several crops, only a few attempts were made to evaluate these Si sources based on their chemical composition. The main objective of this study was to characterize different silicate slags based on their chemical properties and to explore the effect of these chemical properties on the yield, and Si uptake in wetland rice, and dissolution of Si into the soil. Slags were characterised for pH, calcium and magnesium content (alkalinity, A), silicon content, 5 day Na2CO3 + NH4NO3 extractable Si content, and alkalinity to Si ratio (A/Si). Greenhouse and incubation experiments were also conducted using different silicate slags and wollastonite applied at the rate of 300 kg Si ha−1. Slags with A/Si < 3 were found to be ideal Si sources for the economic production of wetland rice and found consistent in increasing soil Si content and rice Si uptake. We conclude that the A/Si ratio of slags can be used as an important parameter to assess the agronomic efficiency of silicate slags in wetland rice.